Adaptation to Climate Change in Industry: Improving Resource Efficiency through Sustainable Production Applications. (1st January 2015) - Alkaya, Emrah; Bogurcu, Merve; Ulutas, Ferda; Demirer, Göksel Niyazi
ABSTRACT: : The objective of this study was to investigate the climate change adaptation opportunities of six companies from different sectors through resource efficiency and sustainable production. A total of 77 sustainable production options were developed for the companies based on the audits conducted. After screening these opportunities with each company's staff, 19 options were selected and implemented. Significant water savings (849, 668 m 3 /year) were achieved as a result of the applications that targeted reduction of water use. In addition to water savings, the energy consumption was reduced by 3, 607 MWh, which decreased the CO2 emissions by 904.1 tons/year. Moreover, the consumption of 278.4 tons/year of chemicals (e.g., NaCl, CdO, NaCN) was avoided, thus the corresponding pollution load to the wastewater treatment plant was reduced. Besides the tangible improvements, other gains were achieved, such as improved product quality, improved health and safety conditions, reduced maintenance requirements, and ensured compliance with national and EU regulations. To the best of the authors' knowledge, this study is the first ever activity in Turkey devoted to climate change adaptation in the private sector. This study may serve as a building block in Turkey for the integration of climate change adaptation and mitigation approach in the industry, since water efficiency (adaptation) and carbon reduction (mitigation) are achieved simultaneously.